DEVELOPMENT OF SCIENCE TEACHING MATERIALS USING INQUIRY BASED LEARNING MODEL ENHANCED AUGMENTED REALITY ON ELEMENTS, COMPOUNDS, AND MIXTURES TOPICS TO DEVELOP CRITICAL THINKING SKILLS OF CLASS VII SMP STUDENTS - Zaroul Mufida; Parno Parno; Muhammad Fajar Marsuki (Jurnal Pembelajaran Sains, 2021)
Material elements, compounds and mixtures are abstract material so that students have difficulty understanding the material. This difficulty is also caused by less attractive learning media. To improve students' critical thinking skills, teaching materials with the help of the media are needed. Media suitable for elements, compounds and mixtures is augmented reality (AR) because it can visualize abstract material. Inquiry based learning is a learning model that is very appropriate for teaching materials using media such as augmented reality (AR). The application of learning using inquiry based learning shows positive results on students' critical thinking skills, especially in science learning. This study aims to produce teaching materials with an inquiry based learning model enriched with augmented reality on elemental material, compounds, and mixtures to develop students' critical thinking skills. Validation test of teaching materials by media expert validators and material experts. Then donevalidation on students. Research and development use the Lee & Owens development model. Research and development are limited to the first three stages, namely assessment / analysis, design and development. The data generated from the validation test and the legibility test state that the teaching materials developed are feasible to be produced.